COMPREHENSION DISORDER OF THE SCHIZOPHRENIC CHARACTER IN THE MOVIE “DONNIE DARKO” - ANGGRAENI, DHIRA (Jurnal Ilmiah Mahasiswa FIB, 2015)
Keywords: Comprehension disorder, Schizophrenia, Schizophrenic, Donnie Darko movie. Language is an instrument of communication that people use to convey message, therefore, it is important for human life. However, in the use oflanguage, there are some problems that make a person has language disorder. One of the issues that deals with language disorder is the main character in the movie “Donnie Darko” suffer from schizophrenia. Based on the phenomenon, this study aims to obtain an understanding and explanation about (1) the positive symptoms of schizophrenia causing comprehension disorder and (2) the types of comprehension disorder suffered by the main schizophrenic character in the movie “Donnie Darko”. This study used descriptive qualitative approach. The data were the utterancesand some scenes that containing comprehension disorder produced by DonnieDarko. In this case, the writer used the journal of schizophrenia in the DSM IV(Diagnostic and Statistical Manual of Mental Disorders, 2000) to analyze the firstproblem about the symptoms of schizophrenia and the theory from Andreasen(1979) to analyze the second problem about the types of comprehension disorder. The findings of this study showed there were 20 data which consisted of 23utterances that contained comprehension disorder produced by the main character in the movie “Donnie Darko”. Moreover, there were 2 positive symptoms of schizophrenia, namely delusion and hallucination which made Donnie Darko experienced comprehension disorder. The types of comprehension disorder suffered by Donnie Darko were poverty of content, tangentiality, derailment, circumstantiality and perseveration. Tangentiality mostly occurred in Donnie Darko utterances.  The writer suggests for the next researchers who want to analyze comprehension disorder to conduct this study by using different subject and theories. Besides, the researcher can also investigate comprehension disorder experienced by a real patient.